Characteristics Of Patient With Foreign Body Ingestion In Palembang - Adelien; Abla Ghanie; Puspa Zuleika; Lisa Apri Yanti (HM Publisher, 2021)
Introduction. Foreign body ingestion is a common diagnosis that presents in emergency departments—coins as the oesophagal foreign body most commonly found in infants and children. Coins retained in the oesophagus require intervention to prevent complications. This study aimed to determine oesophagal coin foreign body patient's characteristic at Mohammad Hoesin General Hospital Palembang. Method. This study design was retrospective descriptive. Samples were all patient diagnosed with oesophagal coin foreign bodies which underwent Extraction with esophagoscopy guidance that was performed at Mohammad Hoesin General Hospital Palembang during January 2013 – August 2017. Result. Forty-three patients had diagnosed with oesophageal coin foreign bodies consist of 22 males and 21 females. The most frequent age was 4fouryears old. The most presenting symptoms are Globus sensation on the throat (79%) and odynophagia (51,1%). Radiologist confirmation was done in every patient with foreign coin bodies in oesophagus. All patients underwent oesophagoscopy. 65,1% of cases of foreign coin bodies were found in the second constriction of throat. Duration of stay in hospital was the range from 1- 4 days, with the most frequent, was two days. There was no complication found in all patients. Conclusion. Oesophagal coin foreign body is most commonly ingested in children. The most presenting symptom is globus sensation on the throat. There is no complication found in this study.